Perlindungan Hukum Pidana terhadap Anak Korban Child Grooming di Ruang Siber: Analisis Kekuatan Delik Siber dalam UndangUndang Perlindungan Anak - Cut Adelia Maharani; Nining Yurista Prawitasari (Jurnal Hukum Lex Generalis, 2026)
The development of information technology increases the risk of child grooming, which is the psychological manipulation of children for the purpose of sexual exploitation. This study analyzes the criminal law protection for child victims of child grooming and the legal certainty of this crime in Indonesia. The results show that legal protection for victims is regulated in the Child Protection Law, the TPKS Law, the ITE Law and the Criminal Code. However, the absence of specific regulations regarding child grooming makes it difficult to prove the element of psychological manipulation, multiple interpretations in the application of norms and less than optimal legal certainty for victims. Therefore, it is necessary to formulate child grooming as a special crime in the Child Protection Law to strengthen legal protection for children in cyberspace.